Systematic Literature Review: Implementation of Game-Based Learning (GBL) Model to Improve Students' Mathematical Creative Thinking Skills - Ade Dwi Oktaviani; Meiliasari Meiliasari; Wardani Rahayu (Examinations: Jurnal Pendidikan Guru Sekolah Dasar, 2025)
This study aims to analyze the implementation of the Game Based Learning (GBL) model in enhancing students’ mathematical creative thinking skills through a Systematic Literature Review (SLR) approach. A total of 100 articles were identified from Google Scholar and Publish or Perish, then screened through the stages of identification, screening, eligibility, and inclusion using the PRISMA guidelines. From this process, 15 articles met the eligibility criteria and were analyzed in depth. The review findings indicate that the GBL model consistently provides positive outcomes in improving students’ mathematical creative thinking abilities. Various game-based media—such as Wordwall, quiz games, board games, digital games, and Construct 2–PhET Simulation-based applications—were proven effective in encouraging students to generate flexible and original ideas, enhance problem-solving skills, and strengthen conceptual understanding in mathematics. Beyond the cognitive domain, GBL also influences the affective and psychomotor domains by improving motivation, learning engagement, and students’ motor coordination. However, the effectiveness of GBL depends on the quality of game design, alignment with the curriculum, availability of technological facilities, and teachers’ competence in managing the learning process. Overall, this study concludes that GBL is an innovative instructional model that effectively supports the development of students’ mathematical creative thinking skills. With sufficient media resources, technological support, and well-prepared teachers, GBL holds strong potential to be optimized as a learning strategy across various educational levels.